2018
DOI: 10.1177/1403494818776168
|View full text |Cite
|
Sign up to set email alerts
|

Irritable bowel symptoms, use of healthcare, costs, sickness and disability pension benefits: A long-term population-based study

Abstract: IBS symptoms influence the long-term use and costs of healthcare, as well as the use of social benefits in the general population. Mental vulnerability explained some, but not all, of the use of healthcare and social benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 27 publications
0
14
0
1
Order By: Relevance
“…82 Additional costs to society might be incurred if patients who are unable to work due to their IBS symptoms claim sickness or disability benefits. In a longitudinal population-based study in Denmark, the expected number of weeks on sickness benefits was 61% higher among those with IBS symptoms, which remained statistically significant following adjustment for age, sex, time in education, comorbidity and mental vulnerability (P=0.01) 83 . There was also a trend towards an increased number of weeks on disability benefits among those with IBS symptoms, compared with people without IBS symptoms, but this difference was not statistically significant following adjusted analysis 83 .…”
Section: [H2] Issues For Societymentioning
confidence: 94%
“…82 Additional costs to society might be incurred if patients who are unable to work due to their IBS symptoms claim sickness or disability benefits. In a longitudinal population-based study in Denmark, the expected number of weeks on sickness benefits was 61% higher among those with IBS symptoms, which remained statistically significant following adjustment for age, sex, time in education, comorbidity and mental vulnerability (P=0.01) 83 . There was also a trend towards an increased number of weeks on disability benefits among those with IBS symptoms, compared with people without IBS symptoms, but this difference was not statistically significant following adjusted analysis 83 .…”
Section: [H2] Issues For Societymentioning
confidence: 94%
“…However a Finish group has repeatedly described absence of associations between health care utilization and mental distress in IBS (101,102). In a Danish study mental vulnerability in IBS patients explained some, but not all, of the use of healthcare and social benefits (103). Further an extensive systematic review regarding health care utilization of patients with IBS and non-ulcer dyspepsia, suggested that symptom severity explains a small proportion of health care seeking behavior.…”
Section: Health Care Utilizationmentioning
confidence: 99%
“…IBS has a negative impact on the quality of life (QOL) and the psychological state of the patient [4]. The disease increases the economic burden on employers as it lowers labor and social capacities of the affected individuals [5,6,7,8]. In general, IBS is a chronic functional gastrointestinal (GI) disorder characterized by recurrent abdominal pain and abnormal bowel habits without structural and biochemical abnormalities [9,10,11].…”
Section: Introductionmentioning
confidence: 99%